Penyuluhan Manfaat Gizi Ikan bagi Kesehatan Anak-Anak di SD Negeri 3 Jirak Kabupaten Sambas - Saputra, Mulpi Iman; Ramadandi, Rizky; Dwiyana, Nida; Rasandi, Rasandi; Atmajaya, Onesimus Dhyas Dwi; Merdekawati, Dewi; Yunita, Nurul Fatimah; Mahyudi S, Indra; Agam, Beryaldi; Maryono, Maryono; Kristiandi, Kiki; Sigiro, Oktavia Nurmawaty (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Fish consumption plays an essential role in fulfilling the nutritional needs of school-aged children, as fish contains high-quality protein, omega-3 fatty acids, vitamins, and minerals that support physical growth and cognitive development. However, children’s low awareness of the nutritional benefits of fish contributes to the low level of fish consumption. This community service activity aimed to increase students' knowledge at State Elementary School 3 Jirak regarding the nutritional content and health benefits of fish. The methods used included interactive lectures, educational videos, discussions, and educational games, supported by pre-test and post-test assessments to measure knowledge improvement. The activity was attended by 23 fifth-grade students. The results showed a significant increase in the average score from 76 on the pre-test to 99 on the post-test, categorized as “Very Good.” Students also demonstrated active participation during the activity, as indicated by their enthusiasm in discussions and educational games. These findings indicate that visual and interactive-based nutrition education is effective in enhancing children's knowledge about the nutritional benefits of fish. This activity is expected to encourage healthier fish consumption habits among students.